200k views
5 votes
Which polynomial expression represents a sum of cubes?

(6 – s)(s2 + 6s + 36)
(6 + s)(s2 – 6s – 36)
(6 + s)(s2 – 6s + 36)
(6 + s)(s2 + 6s + 36)

2 Answers

4 votes

Answer: (6 + s)(s^2 – 6s + 36)

Explanation:

User Woodham
by
5.6k points
6 votes

Answer:

(6 + s)(s² - 6s + 36)

Explanation:


\text{The sum of cubes:}\\\\a^3+b^3=(a+b)(a^2-ab+b^2)\\\\\text{Therefore}\\\\\text{for}\ a=6\ \text{and}\ b=s:\\\\6^3+s^3=(6+s)(6^2-6s+s^2)=(6+s)(36-6s+s^2)

User Ashish Joseph
by
5.1k points